Wind-induced response characteristics of a yawed and inclined cable in ABL wind: Experimental- and numerical-model based study. (1st July 2020) - Jafari, Mohammad; Sarkar, Partha P.
Highlights: Study of wind-induced response characteristics of an inclined/yawed cable in ABL wind. Reproduce response behavior of a full-scale cable by testing an aeroelastic model. Effect of sag ratio, cable tension, inclination, and yaw angles on cable's excitation. Observation of first, second, and third vibration modes for a flexible smooth cable. FEA to estimate the aerodynamic damping using the section-model wind tunnel data. Abstract: Inclined cables used in bridges or other infrastructures are vulnerable to unsteady wind-induced loads producing moderate- to large-amplitude vibration that may result in damage or failure of the cables, resulting in catastrophic failure of the structure they secure. In the present study, wind-induced response of an inclined smooth cable was studied through wind tunnel measurements using a flexible cable model for a better understanding of the vibration characteristics of structural cables in atmospheric boundary layer wind. For this purpose, in-plane and out-of-plane responses of a sagged and a non-sagged flexible cable were recorded by four accelerometers. Four cases with different yaw and inclination angles of a cable with approximate sag ratios of 1/10 were studied to investigate the wind directionality effect on its excitation mode(s) and response amplitude. Cable tension was also measured during all experiments to assess the correlation of wind speed, excitation vibration mode, and natural frequency of the cable with change in cable tension. Additionally, two inclined cables with no sag were tested to determine the influence of sag of a cable on its vibration characteristics. In the second part of this study, a series of finite element analyses were conducted to predict the wind-induced aerodynamic damping of an inclined bridge cable. Experimental results showed that excitation mode(s) of a cable depend on wind speed, inclination angle, and sag ratio and cable tension. First, second, and third vibration modes were observed at a low wind speed for different test cases, whereas higher vibration modes were observed to contribute to the cable response at high wind speeds. Moreover, it was seen that the cable tension significantly increased with wind speed resulting in increased value of the excited natural frequency. Numerical results obtained through finite element analysis of an inclined full-scale cable showed that the criteria that are based on section models can underestimate the critical reduced velocity for dry cable galloping.